To have and to heist ebook - Desai, Sara (2023)
To exonerate her best friend, one woman must mastermind a jewelry heist during the wedding of the season in this hilarious romantic-comedy caper from the author of The Dating Plan .  Simi Chopra is on a bad-luck streak. She’s lost yet another job, her student loan debt won’t stop growing, her basement apartment is a certifiable flood zone, and now her best friend has been accused of stealing a multimillion-dollar diamond necklace. To put it lightly, she’s desperate for a break—that’s right when Jack waltzes out of the bushes and into her life. Jack is just as charming as he is mysterious. When he offers to help her find the missing necklace and steal it back, Simi jumps at the chance to clear her friend’s name and collect the substantial reward. But every good heist needs a crew. All she needs to do is transform a ragtag group of strangers into an elite heist crew, infiltrate a high-society wedding and steal the necklace from a dangerous criminal before the happy couple say "I do." Meanwhile the bride is keeping secrets, a detective with a slow-burn smile keeps showing up at her door, and the ultimate robbery might not be the wedding con, but the way Jack is stealing her heart.